Penerapan Sistem Aplikasi Pengelolaan Materi Pembelajaran Pada Yayasan Al-Mabrur Kabupaten Bekasi - Fitriyani, Aida; Hendharsetiawan, Andy Achmad; Atika, Prima Dina; Sari, Rafika (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Information technology that continues to grow rapidly, especially in the field of education, requires the parties involved to be able to adapt to technology. Especially in the last two years, Indonesia has experienced the Covid-19 Pandemic, which requires the teaching and learning process to be transformed into an online form, giving rise to many e-Learning platforms. Using e-Learning can help teachers and students monitor the activity of students in doing assignments, discussion forums or other activities. This online learning process was also carried out at the Foundation for Orphans and Dhuafa Al-Mabrur Kebalen, Bekasi Regency. To assist the Foundation in implementing e-Learning, this Community Service (PKM) program was carried out which aims to develop Learning Management System (LMS) software. This training is expected to meet several targets, namely being able to manage learning materials and being able to manage e-Learning participant accounts. From the results of the training on the use of Web-based applications, it shows that teachers find it helpful to monitor student activities in accessing online learning materials. The students have also been able to use this eLearning application well.